МОРФОБИОЛОГИЧЕСКОЕ ОПИСАНИЕ СЕРОГО ГОЛЬЦА TRIPLOPHYSA DORSALIS ИЗ РЕКИ БЕСАГАШ (Experimental biology, 2009)
Biological features and morphological characteristics of the gray stone loach Triplophysa dorsalis from the Besagash river (Balkhash lake basin) had been investigated. Many of indexes are variable. Investigated counted features are rather stable. In spite of the good food supplement living conditions are not suitable enough for the gray stone loach.
Keywords: morphological characteristics